A comprehensive review of physicochemical properties, production process, performance and emissions characteristics of 2nd generation biodiesel feedstock: Jatropha curcas. (1st February 2021) - Singh, Digambar; Sharma, Dilip; Soni, S.L.; Inda, Chandrapal Singh; Sharma, Sumit; Sharma, Pushpendra Kumar; Jhalani, Amit
Graphical abstract: Highlights: Classification of biodiesel generations on the basis of the type of feedstocks is covered. Botanical description and growth condition requirements of jatropha are discussed. Physicochemical properties and fatty acid profile of jatropha biodiesel are analyzed. Production of biodiesel from jatropha oil with different techniques is summarized. Performance and emissions characteristics of C.I. engine fuelled with jatropha biodiesel are reviewed. Abstract: Due to limited reserves of conventional fossil fuels and their negative impact on global climate and human health, researches are focused to find the alternate energy substitute. Comparable properties of biodiesel make it one of the most promising alternatives of conventional diesel fuel. Jatropha curcas oil (non-edible oil) belongs to the second-generation of biodiesel. In this review, the physicochemical properties, fatty acids distribution, stability of jatropha oil are discussed in detail. The change in fatty acid profile affects the fuel properties, performance and emissions of diesel engines operated on jatropha biodiesel. Oxidation stability of jatropha biodiesel is poor due to the high amount of unsaturated fatty acids. Blending, thermal cracking, micro-emulsification, and transesterification are four basic approaches for production of biodiesel. Transesterification is the most adoptive method due to less expensive operation and high product yield. This article also highlighted the performance and emissions of compression ignition engines operated on jatropha biodiesel and its blends. The lower calorific value of jatropha biodiesel is responsible for the decrease in brake thermal efficiency and an increase in brake specific fuel consumption. High availability of oxygen in jatropha biodiesel reduces HC, CO, and PM emissions, while NOx emission increases significantly. This article provides the most of details of optimum parameters for jatropha biodiesel production and its efficient use in diesel engines.